A Predictive Model of Innovation in Rural Entrepreneurship. (2015) - Elena, Harpa; Sorina, Moica; Rus, Dana
Abstract: The present research started from the declared objective of increasing the visibility of rural entrepreneurship conceived in a new manner, which should highlight the innovative potential of local entrepreneurs as a condition of success and as a condition of accomplishing the level of well-being. The approach is justified by the identification of the role of innovation in shaping the profile of local entrepreneurs, the need for theoretical models which should illustrate conceptually and practically the relation between the level of innovation and the successful development of the business. The study started from underlining the main factors which determine economic development in the rural environment. The main objective of the study is to define a predictive model in the scope of sustaining innovative development among the investigated entrepreneurs.